Constructing Grounded Theory - Charmaz, Kathy (SAGE Publications, Ltd. (UK), 2014)
Kathy Charmaz presents the definitive guide to doing grounded theory from a constructivist perspective. This second edition of her groundbreaking text retains the accessibility and warmth of the first edition whilst introducing cutting edge examples and practical tips. This expanded second edition: - explores how to effectively focus on data collection - demonstrates how to use data for theorizing - adds two new chapters that guide you through conducting and analysing interviews in grounded theory - adds a new chapter on symbolic interactionism and grounded theory - considers recent epistemological debates about the place of prior theory - discusses the legacy of Anselm Strauss for grounded theory. This is a seminal title for anyone serious about understanding and doing grounded theory research.